The River In Senganan Village As A Source Of Ideas For The Creation Of Paintings - Kanta, Putu Aripta Dera; Setem, I Wayan; Yudha, I Made Bendi (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
This Independent Study TA thesis has the theme "Rivers In The Village Senganan As A Source (De Creating Works Of Painting"), departs from an idea about the river as a source of life for the community in Senganan village. From this, it gives rise to the urge to present natural visualizations with beautiful forms by combining certain techniques and references to achieve the goal and the desired meaning. The problem faced is how to process visuals to represent ideas. ideas, so that changes to the work look interesting. The tuivan and its benefits are to provide a new reflection for the community to better protect and preserve the river in Senganan village. To answer what is the aim of this work, the creation method involves exploration, improvisation and formation. By compiling elements of fine art, and through exploration, improvisation, and formation stages, and combined with ideas and ideas, 6 works were created entitled: 1) "Natural Water", 2) "Waterfall in the Forest", 5) "To river towards one point", 4) "Mysterious stone", 5) "Destruction of the river", 6) "The power of water". In accelerating the work, the author will use several references and techniques from artists. By combining impressionist techniques and expressionist techniques using paint acrylic, in visualizing works that embody the beautiful nature of rivers up to the pollution of these rivers as time goes by, various techniques are combined neatly to create aesthetic works, it is hoped that they can produce quality works and become the author's identity. In the end, it can be concluded that humans are very dependent on nature, and we must trade with nature to be sustainable. The river in Senganan village provides a lot of inspiration for creative work and is very interesting to use and develop with imaginative ideas that will become valuable and meaningful works. By creating this work, the author hopes to be able to convey a message or meaning regarding the personal phenomena that the author has experienced.